The Culture of Poverty Alleviation——A New Examination and Reflection on Poverty Relief and Development from the Culture of Poverty Viewpoint - Zhang Shiding (Contemporary Social Sciences, 2017)
In order to drive progress toward the completion of building a comprehensively well-off society, poverty reduction has become a top priority on the agendas of poverty stricken areas. Paths that can help advance and improve poverty reduction are diverse, and the culture of poverty alleviation is a choice in this context. From the perspective of the culture of poverty, this paper attempts to probe the poverty situation in poverty stricken areas and identify the factors that contribute to the condition such as antiquated ideas and mindsets, limited schooling, and negative values of the people inhabiting these areas, which hinder them from casting off poverty. Therefore, in carrying out the work of poverty alleviation, we must bear in mind several important aspects like system building, transformation of people' s mindsets, development of a culture of industry and the effective supply of educational resources. We must examine and reflect on the work rationally. Only then will the effort contribute to realizing the ultimate goal of overall poverty reduction